The Difference of allergic reaction on hand sanitizer gel and liquid among nurses at RSU Karsa Husada Batu - Adilah, Lilah (Jurnal Keperawatan, 2023)
Introduction: The program to improve the hand hygiene of health workers has been declared by WHO through a patient safety program that sparked the Global Patient Safety Challenge "clean care is safe care". Hand hygiene practice, health workers may use the gel or liquid form of hand sanitizer with alcohol-based ingredients. However, alcohol is flammable, causing dryness and irritation of the skin on repeated use and increases the risk of viral infections that trigger inflammation of the digestive tract. Objectives:  Researcher would like to find any difference on allergic reaction between the use of hand sanitizer gel and liquid form which were commonly used by nurses at RSU Karsa Husada Batu during hand hygiene practice. Methods:  The research design used is a survey research with a cross sectional approach where the researcher observes the research subjects using a check list and questionnaire, with a sample of 80 respondents. The data analysis used non-parametric statistics Mc-Nemar test. Results: The results of the Mc-Nemar Test showed a p value of 0.033 < 0.05 which means that the use of hand sanitizer gel and liquid has a significant difference in the allergic reaction among nurses. Conclusions:  Hand sanitizer in gel or liquid form were safe as long as use correctly and properly, also selecting a type of hand sanitizer must be matched with the individual skin